2018
DOI: 10.1002/ar.23913
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Expression Profiles of Sox9 in Embryonic, Post Natal, and Adult Heart Valve Cell Populations

Abstract: Heart valves are dynamic structures and abnormalities during embryonic development can lead to premature lethality or congenital malformations present at birth. The transcription factor Sox9 has been shown to be critical for early and late stages of valve formation, but its defined expression pattern throughout embryonic, post natal and adult growth and maturation is incomplete. Here we show that in the developing embryo, Sox9 is not detected in valve endothelial cells lining the primitive valve structures, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…We found that SOX9 was expressed in a few aortic VECs (Figure 6A, arrows) and weakly in the VICs (Figure 6A, arrowheads) of adult control mice as previously reported. 43 In contrast, SOX9 was strongly upregulated in the VICs of Prox1 ∆VEC mice (Figure 6A). SOX9 expression was also significantly upregulated in the aortic VICs of 6-month-old Tie2-Cre; Pdgfrb +/LSL-D849V mice (Figure 6B).…”
Section: Resultsmentioning
confidence: 95%
“…We found that SOX9 was expressed in a few aortic VECs (Figure 6A, arrows) and weakly in the VICs (Figure 6A, arrowheads) of adult control mice as previously reported. 43 In contrast, SOX9 was strongly upregulated in the VICs of Prox1 ∆VEC mice (Figure 6A). SOX9 expression was also significantly upregulated in the aortic VICs of 6-month-old Tie2-Cre; Pdgfrb +/LSL-D849V mice (Figure 6B).…”
Section: Resultsmentioning
confidence: 95%
“…Recent work in mice demonstrated that following EMT, mesenchymal cells activate expression of the Sox9 transcription factor in the population of cells that differentiate as VICs [36]. In embryonic stages, Sox9 is not expressed in VECs, and thus may provide a genetic handle to identify additional genes required for VIC differentiation.…”
Section: Mesenchymal Cells Populate the Endocardial Cushionsmentioning
confidence: 99%
“…A critical role for Sox9 in proliferation of valve precursor cells was suggested by targeted loss of function mice, which display severely hypoblastic endocardial cushions [37]. Sox9 has later embryonic roles in ECM remodeling later in valve development, and following birth, becomes expressed in VECs as well as maturing VICs [36].…”
Section: Mesenchymal Cells Populate the Endocardial Cushionsmentioning
confidence: 99%
“…Implantation of bFGF under the skin of mice can induce angiogenesis. Due to the high-water content in the gel, the degradation rate is fast, the release of bFGF is fast, and the induction time of angiogenesis is very short (9). Wiktor transplanted bFGF hydrogel under the skin of mice and observed the formation of new blood vessels around the implant.…”
Section: Introductionmentioning
confidence: 99%